Wpływ w stosunkach międzynarodowych - Maj, Czesław (Przegląd Politologiczny, 2018)
Influence is synonymous, and sometimes even perceived as equivalent, with power. While power is a relationship of authority and subordination, and hence the decisions of power are of a subordinating nature, influence does not stem from coercion or subordination. Another difference lies in the possibility of mutual interactions between the influencing entities. While a power wielder is of a concentrated nature (regardless of whether it is an individual or an authority comprised of many people), the influencing entities can also assume deconcentrated forms. There is a potential for mutual dependency. The voluntary nature of subordination should not be ignored. An influencing entity does not have at its disposal the array of decision enforcement instruments which are typical of power. Instead, it uses attractiveness, persuasion, social modelling, systems of values, etc.